Application of Geochemical Technique in Exploration and Evaluation of Copper, Lead and Zinc Resources of Nepal - Jnawali, B. M.; Amatya, K. M. (Journal of Nepal Geological Society, 1993)
Application of Geochemical technique in mineral exploration was used in Nepal during 1975-1985 by the Mineral Exploration Development Board (MEDR). Systematic drainage reconnaissance over 40,000 km2 area resulted in the recognition of a large number of anomalies several of which are related to previously unknown mineralizations. The anomalies were categorized into 1 to 4 assessed on the basis of magnitude, homogeneity, area and potential host rock. All anomalies of category 1 and 2 that were investigated by follow-up stream sediment and soil geochemistry of varying stages were finally found to disclose the mineralized sources. In all cases, detailed grid soil sampling results in conjunction with geologic observations enabled to ascertain the location, extent and continuity of sub outcropping bedrock source with considerable precision, but it was not possible to make reliable estimate of grade. It has been attempted to evaluate the base metal resource based on the data available of the MEDR work as well as Department of Mines and Geology (DMG) and others. Although no economic deposits have been discovered except Ganesh Himal Zinc Lead, about 20 base metal prospects have been drilled and tonnage and grade proved and estimated. Of these, Kalitar Copper and Wapsa Copper deposits are considered to be of marginal economic grade, while the rest are inventoried a deposits of subeconomic to non-economic grade.